Principle of realization of the practice sessions of module 5 «Reconstructive surgery of maxillofacial area» in terms of credit-modular educational system - Halahdina, A. A.; Herasym, L. M. (Journal of Education, Health and Sport, 2019)
The article highlights the methodology of realization of the practice sessions of module 5 «Reconstructive surgery of maxillofacial area» for students other 5th year, dental faculty, in the Higher State Educational Establishment of Ukraine«Bukovinian State Medical University».